English Teachers’ Readiness for Technology Integrated Learning: Perceptions in The Context of a Changing Educational Era - Zahro, Siti Fatimatus; Hidayah, Waqiatun Nurul; Zam-zam, Zulfani Muhammad (Proceeding International Conference on Education, 2025)
The rapid advancement of digital technology has transformed English language teaching (ELT), requiring teachers to possess not only content expertise but also technological and pedagogical competence. This qualitative case study explores how Indonesian junior high school English teachers perceive and respond to the integration of technology in their teaching practice. Grounded in Sociocultural Theory, the Technology Acceptance Model (TAM), Technological Pedagogical Content Knowledge (TPACK), Diffusion of Innovation Theory, and Constructivist Learning Theory, the study involved six purposively selected teachers with at least one year of experience. Data were gathered through semi-structured interviews and analyzed thematically. The findings reveal that teachers generally hold positive attitudes toward digital technology, recognizing its potential to enhance interactivity, engagement, and instructional quality. However, they also face significant challenges. First-order barriers such as insufficient training, limited infrastructure, and institutional neglect coexist with second-order barriers including lack of confidence and limited digital literacy. Furthermore, technology alone was not seen as a guarantee for student motivation or learning outcomes without clear pedagogical planning. Despite these constraints, teachers displayed strong adaptability by engaging in self-directed learning through platforms like YouTube and TikTok, experimenting with digital tools such as Quizizz and Duolingo, and participating in informal peer mentoring. They also emphasized the need for ongoing, practical, and context-specific professional development. This study highlights the multifaceted nature of teacher readiness in digital learning and calls for systemic support through targeted training, infrastructure provision, and collaborative learning cultures to ensure meaningful technology integration in ELT contexts.